Efeitos imunomodulatório e neuroprotetor da aplicação de células tronco mesenquimais alogênicas criopreservadas em ratos com trauma experimental de medula espinhal - Isabel Rodrigues Rosado (2015)
The aim of the present study was to evaluate immunomodulatory and neuroprotective effects of cryopreserved allogenic mesenchymal stem cells (MSCs) aplication on experimental spinal cord injury. Therefore, Rattus norvegicus, Lewis, EGFP, were used for MSCs isolation, and Wistar for the spinal cord injury study. Three experimental groups were evaluated: negative control (NC), positive control (CP) and MSC, on five evaluation time: 24, 48, 72 hours and eight and 21 days after surgery. Motor function was assessed by BBB locomotor rating scale. Histopathology and immunohistochemistry were performed for measurement of inflammatory infiltration (CD68), of neuronal integrity (NeuN) and astrocyte activation (GFAP). IL-10, TNF-, IL-1, TGF-, BDNF, GDNF and VEGF gene transcripts measurement were performed by real time RT-PCR. When compared to the CP group, the MSC group showed higher motor function scores at 72 hours, 8 and 21 days, lesser CD68 expression at eight days and GFAP at 21 days. Furthermore, there was lesser white matter degeneration and higher NeuN expression in MSC group at 21 days. IL-10 expression was higher in the MSC group at 24 hours, GDNF 48 hours and 8 days and VEGF at 21 days. However it was observed in the MSC group lower TNF- expression at 8 and 21 days, and TGF- 24 hours and at 21 days. There were no differences in IL-1 and BDNF expression. The MSC administration reduced the inflammatory infiltrate, increased t neuronal integrity, decreased white matter degeneration and astrocytes activation after spinal cord injury. Additionally, the MSC increased IL-10, GDNF and VEGF expression, and the reduced TNF and TGF-.